Bifurcation and control for a discrete-time prey-predator model with Holling-IV functional response - Chen, Qiaoling; Teng, Zhidong; Hu, Zengyun (Zielona Góra: Uniwersytet Zielonogórski)
The dynamics of a discrete-time predator?prey model with Holling-IV functional response are investigated. It is shown that the model undergoes a flip bifurcation, a Hopf bifurcation and a saddle-node bifurcation by using the center manifold theorem and bifurcation theory.
Keywords: discrete prey?predator model; flip bifurcation; Hopf bifurcation; saddle-node bifurcation; OGY chaotic control